Nuclear power - Breeze, Paul A. (The power generation series, 2017)
Nuclear Power provides a concise, up-to-date, accessible guide to the most controversial form of power generation. The author includes a comprehensive description of the various methods for generating nuclear power and evaluates the political, strategic, environmental, economic, and emotional factors involved in each method. The analysis of real-life, tragic examples, such as the accidents in Chernobyl and Fukushima help the reader understand the associated risks and dangers of this method of power generation and the radioactive waste it creates. This is a valuable and insightful read for those involved in nuclear power, including power plant designers and engineers, as well as those involved in the protection of society and the environment.--Provided by publisher.